In-situ synthesis of monodispersed Au nanoparticles on eggshell membrane by the extract of Lagerstroemia speciosa leaves for the catalytic reduction of 4-nitrophenol. (5th October 2018) - Chang, Weidan; Liu, Shili; Qileng, Aori; Liu, Weipeng; Liu, Yingju
Abstract: A facile, green and in situ synthesis for the immobilization of monodispersed Au nanoparticles (Au NPs) on eggshell membrane (ESM) using the Lagerstroemia speciosa leaves extract (LSE) was reported. The stable fibrous-network structure of the ESM offered great surface area and abundant functional groups to provide an ideal support, while the leaves extract of Lagerstroemia speciosa can act as stabilizing and reducing reagents for Au NPs without capping reagents or heating. The morphology and surface chemical information were characterized via transmission electronic microscopy (TEM), field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), x-ray photoelectron spectroscopy (XPS), x-ray diffraction analysis (XRD) and thermogravimetric analysis (TGA). The catalyst exhibited excellent performance for the reduction of 4-nitrophenol (4-NP), showing that ESM@LSE@Au from a 0.6 mM Au precursor exhibited the best catalytic activity with the reaction rate constant of 29.70 s −1 · g −1 and a conversion of over 99.84% in 6 min. Moreover, the catalyst can be efficiently recycled by mild centrifugation with a remained conversion over 92.40% after 10 cycles, suggesting the potential for the reduction of nitroaromatic compounds.